ILC2s regulate adaptive Th2 cell functions via PD-L1 checkpoint control. - Schwartz, Christian; Khan, Adnan R.; Floudas, Achilleas; Saunders, Sean P.; Hams, Emily; Rodewald, Hans-Reimer; Mckenzie, Andrew N. J.; Fallon, Padraic G. (Journal of Experimental Medicine, 2017)
Our results identify a novel PD-L1-controlled mechanism for type 2 polarization, with ILC2s mediating an innate checkpoint to control adaptive T helper responses, which has important implications for the treatment of type 2 inflammation.